THE RELATIONSHIP BETWEEN MATERNAL NUTRITIONAL KNOWLEDGE AND FEEDING PATTERNS IN STUNTED TODDLERS - Wardani, Karmila Ayu; Rambung, Etha; Wartiningsih, Minarni; Wirjatmadi, Bambang (E-Jurnal Medika Udayana; Vol 13 No 3 (2024): E-Jurnal Medika UdayanaDO - 10.24843/MU.2024.V13.i03.P18, 2024)
The nutrients in the food consumed play a role in determining a person's condition and nutritional status. This research aims to determine the description and relationship between the level of maternal nutritional knowledge and the feeding patterns of mothers who have stunted toddlers in Desa Sumorame Candi Sidoarjo . This research method is analytical observational with a cross sectional approach. The research subjects were 40 mothers of stunted toddlers in Sumorame Candi Sidoarjo Village. Data collection used a questionnaire with guided interviews. Data were analyzed using the Chi-square test (significance ?<0.05). Data shows the percentage of mothers with high levels of knowledge about nutrition (5%), medium (27.5%), and low (67.5%) while mothers with appropriate (47.5%) and inappropriate feeding patterns (52, 5%). The chi-square statistical test results showed a relationship between the mother's level of knowledge and toddler feeding patterns (p=0.027). The research concludes that the mother's level of knowledge about nutrition influences the mother's feeding pattern for her toddler.